# A 1 x x2 2 x3 3 x4 4 x x3 3 x5 5

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: (a2 − a3 ) + (a3 − a4 ) + · · · + (an − an+1 ) which is a telescoping sum, sn = a1 − an+1 = 2 − 2n+1 (2/3)n+1 , lim s = lim 2 − = 2. n+1 n→+∞ n n→+∞ −2 1 − (2/3)n+1 3n+1 EXERCISE SET 11.4 ∞ 1. (a) k=1 ∞ (b) k=1 ∞ k=1 ∞ 2. (a) k=2 ∞ 1/2 1 = 1; = 2k 1 − 1/2 k=1 1/5 1 = 1/4; = 5k 1 − 1/5 1/4 1 = 1/3; = 4k 1 − 1/4 ∞ k=1 1 =1 k (k + 1) k=1 1 1 +k 2k 4 = 1 + 1/3 = 4/3 (Example 5, Section 11.3); 1 1 = 1/4 − 1 = −3/4 − 5k k (k + 1) 1 = 3/4 (Exercise 10, Section 11.3); k2 − 1 ∞ so k=2 ∞ k=2 7/10 7 = 7/9; = 10k−1 1 − 1/10 7 1 − = 3/4 − 7/9 = −1/36 k 2 − 1 10k−1 ∞ (b) with a = 9/7, r = 3/7, geometric, k=1 ∞ with a = 4/5, r = 2/5, geometric, k=1 ∞ ∞ 7−k 3k+1 − k+1 2 k=1 5k 7−k 3k+1 = 9/7 = 9/4; 1 − (3/7) 4/5 2k+1 = 4/3; = k 5 1 − (2/5) = 9/4 − 4/3 = 11/12 3. (a) p = 3, converges (b) p = 1/2, diverges (c) p = 1, diverges (d) p = 2/3, diverges 4. (a) p = 4/3, converges (b) p = 1/4, diverges (c) p = 5/3, converges (d) p = π , converges Exercise Set 11.4 372 1 k2 + k + 3 = ; the series diverges. k→+∞ 2k 2 + 1 2 5. (a) (b) lim lim cos kπ does not exist; (c) (d) k→+∞ lim k→+∞ 1+ 1 k k = e; the series diverges. 1 = 0; no information k→+∞ k ! lim the series diverges. k = 0; no information k→+∞ ek 6. (a) (b) lim 1 (c) lim √ = 0; no information k→+∞ k +∞ (d) 1 1 = lim ln(5x + 2) →+∞ 5 5x + 2 7. (a) 1 +∞ 1 √ lim √ k→+∞ k = 1; the series diverges. k+3 = +∞, the series diverges by the Integral Test. 1 1 1 tan−1 3x dx = lim 2 →+∞ 3 1 + 9x (b) lim ln k = +∞; the series diverges. k→+∞ = 1 1 π /2 − tan−1 3 , 3 the series converges by the Integral Test. +∞ x 1 ln(1 + x2 ) dx = lim →+∞ 2 1 + x2 8. (a) 1 +∞ (b) = +∞, the series diverges by the Integral Test. 1 √ = 1/ 6, √ (4 + 2x)−3/2 dx = lim −1/ 4 + 2x →+∞ 1 1 the series converges by the Integral Test. ∞ 9. k=1 ∞ 10. k=1 1 = k+6 3 = 5k ∞ k=1 12. ∞ k=1 3 5 1 , diverges because the harmonic series diverges. k 1 1 √ , diverges because the p-series with p = 1/2 ≤ 1 diverges. = k + 5 k=6 k 1 lim k→+∞ e1/k +∞ 13. = 1, the series diverges because lim uk = 1 = 0. k→+∞ 3 (2x − 1)2/3 →+∞ 4 (2x − 1)−1/3 dx = lim 1 14. k=7 1 , diverges because the harmonic series diverges. k ∞ √ 11. ∞ +∞ ln x is decreasing for x ≥ e, and x 3 = +∞, the series diverges by the Integral Test. 1 ln x 1 = lim (ln x)2 →+∞ 2 x = +∞, 3 so the series diverges by the Integral Test. 15. lim k→+∞ +∞ 16. 1 k 1 = lim = +∞, the series diverges because lim uk = 0. k→+∞ ln(k + 1) k→+∞ 1/(k + 1) 2 2 1 xe−x dx = lim − e−x →+∞ 2 = e−1 /2, the series converges by the Integral Test. 1 373 17. 18. Chapter 11 lim (1 + 1/k )−k = 1/e = 0, the series diverges. k→+∞ k2 + 1 = 1 = 0, the series diverges. k→+∞ k 2 + 3 lim +∞ tan−1 x 1 tan−1 x dx = lim →+∞ 2 1 + x2 19. 1 2 = 3π 2 /32, the series converges by the Integral Test, since 1 1 − 2x tan−1 x d tan−1 x = &lt; 0 for x ≥ 1. 2 dx 1 + x 1 + x2 +∞ √ 20. 1 21. 1 dx = lim sinh−1 x →+∞ x2 + 1 = +∞, the series diverges by the Integral Test. 1 lim k 2 sin2 (1/k ) = 1 = 0, the series diverges. k→+∞ +∞ 22. 1 3 3 1 x2 e−x dx = lim − e−x →+∞ 3 = e−1 /3, 1 the series converges by the Integral Test (x2 e−x is decreasing for x ≥ 1). 3 ∞ 23. 7 k −1.01 , p-series with p &gt; 1, converges k=5 +∞ 24. 25. = 1 − tanh(1), the series converges by the Integral Test. sech2 x dx = lim tanh x →+∞ 1 1 +∞ 1 dx is decreasing for x ≥ e−p , so use the Integral Test with to get p p x(ln x) e−p x(ln x) +∞ if p &lt; 1 1−p (ln x) = +∞ if p = 1, lim = lim ln(ln x) −1 →+∞ →+∞ 1 − p e−p if p &gt; 1 e−p (−1)p pp (p − 1) Thus the series converges for p &gt; 1. 26. Set g (x) = x(ln x)[ln(ln x)]p , g (x) = (1 + ln x) ln(ln x) + p, so for ﬁxed p there exists A &gt; 0 such +∞ dx that g (x) &gt; 0, 1/g (x) is decreasing for x &gt; A; use the Integral Test with x(ln x)[ln(ln x)]p A to get +∞ if p &lt; 1, [ln(ln x)]1−p lim ln[ln(ln x)] = +∞ if p = 1, lim = 1 →+∞ →+∞ 1−p if p &gt; 1 A A (p − 1)[ln(ln A)]p−1 Thus the series converges for p &gt; 1. ∞ 27. (a) 3 k=1 ∞ (c) k=2 1 − k2 ∞ k=1 1 = (k − 1)4 1 = π 2 /2 − π 4 /90 k4 ∞ k=1 1 = π 4 /90 k4 ∞ (b) k=1 1 1 − 1 − 2 = π 2 /6 − 5/4 2 k 2 Exercise Set 11.4 374 28. (a) Suppose Σ(uk + vk ) converges; then so does Σ[(uk + vk ) − uk ], but Σ[(uk + vk ) − uk ] = Σvk , so Σvk converges which contradicts the assumption that Σvk diverges. Suppose Σ(uk − vk ) converges; then so does Σ[uk − (uk − vk )] = Σvk which leads to the same contradiction as before. (b) Let uk = 2/k and vk = 1/k ; then both Σ(uk + vk ) and Σ(uk − vk ) diverge; let uk = 1/k and vk = −1/k then Σ(uk + vk ) converges; let uk = vk = 1/k then Σ(uk − vk ) converges. ∞ 29. (a) diverges because ∞ (2/3)k−1 converges and 1/k diver...
View Full Document

## This document was uploaded on 02/23/2014 for the course MANAGMENT 2201 at University of Michigan.

Ask a homework question - tutors are online